MINERALOGY OF BLOOMERY SLAGS OF THE SHUVAKISH IRONWORKS PLANT (OUTSKIRTS OF YEKATERINBURG, SVERDLOVSK OBLAST) - Yu.V. Erokhin; A.V. Zakharov; L.V. Leonova (Минералогия)
The mineralogy of slags of the Shuvakish ironworks plant is studied. The plant had been operated during the reign of Peter the Great from 1704 to 1716 years and was located within the presentday northwestern outskirts of Yekaterinburg. The slags are composed of fayalite aggregate with a significant content of hercynite and wüstite and contain spherules of iron, glass, leucite and ferromerrillite. The chemical composition of rock-forming and ore minerals is determined on a JSM-6390LV (Jeol) SEM equipped with an INCA Energy 450 X-Max 80 EDS (Oxford Instruments) (Institute of Geology and Geochemistry UB RAS, Yekaterinburg). The slags formed as a result of bloomery iron production. Their formation temperature is estimated in a range of 1177 °С on the basis of eutectic crystallization of wüstite and fayalite. The Shuvakish plant was supplied with marsh iron ore, which was most likely extracted in the nearest Moleben swamp located to the north from the plant.